Technological Applications of the New Theory of Dynamic Interactions (Global Journals of Research in Engineering, 2013)
The aim of this paper is to present given technological applications of the Theory of Dynamic Interactions a theory that has been the object of my investigation and embodies a new scientific approach to Rotational Dynamics The method utilized in the development of this theory and its applications consists of a scientific analysis of the dynamic fields that are generated in bodies subjected to simultaneous non-coaxial rotations The results obtained in the development of this dynamic theory allow an innovative approach to significant scientific and technological applications for example in orbital dynamics orbit determination and orbit control As a conclusion under the Theory of Dynamic Interactions various new assumptions have been elaborated based on the analysis of inertial fields generated A new criteria has been found applicable in the understanding of the coupling of velocity fields The innovative dynamic theory that has been developed based on new concepts such as rotational inertia or field s coupling has numerous technological applications in accelerated rotation systems
Keywords: development of this theory; and its applications; consists of a scientific analysis of dynamic